2009
DOI: 10.4067/s0717-97072009000100008
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Copper, Chromium and Lead Content in Mugil Cephalus and Eleginops Maclovinus Obtained in the Mouths of the Maule and Mataquito Rtvers (Maule Region, Chile)

Abstract: The Cu, Cr and Pb concentrations were determined in Mugil cephalus and Eleginops maclovinus, fish species inhabiting the mouths of the Maule and Mataquito Rivers (Maule Region, Chile) which are consumed by the coastal population in large quantities. Measurements were taken by flame atomic absorption spectroscopy to analyse representative muscle tissue of the two species. The method was validated using certified reference material (DOLT-1). The concentration ranges of Cu, Cr and Pb (mg . kg -1 , dry weight) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Methods for sample preparation and analysis were similar to those used by Tapia et al (2006Tapia et al ( , 2009Tapia et al ( , 2010, weighing and measuring all the specimens obtained. The fish were gutted and sexed using plastic material, and part of the liver and muscle tissue was extracted.…”
Section: Sample Takingmentioning
confidence: 99%
“…Methods for sample preparation and analysis were similar to those used by Tapia et al (2006Tapia et al ( , 2009Tapia et al ( , 2010, weighing and measuring all the specimens obtained. The fish were gutted and sexed using plastic material, and part of the liver and muscle tissue was extracted.…”
Section: Sample Takingmentioning
confidence: 99%
“…Human activities associated with mining industries, such as metal-rich mine tailing and mineral deposits, are important sources of polluting compounds that decrease water quality in several river basins in the northerncentral region of Chile [18,[20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…While the sources of Cr in the study sites are unclear, it is common to nd Cr levels higher in water bodies that receives e uents from electroplating, dyeing, or printing industries 43 , most of which are found in the Western Division which includes Ba Province. A similar study of Cr levels in mullet from the Maule Region, Chile, found mean concentrations at 2.4 mg/kg (dry weight) [min-max: 0.3 ± 0.1-6.3 ± 0.7 mg/kg dry weight] 44 . Comparatively, the ndings in this study are in the lower ranges of Cr concentration than what was detected by Tapia, et al 44 .…”
Section: Discussionmentioning
confidence: 86%